O SILÊNCIO CONSTITUTIVO DE SENTIDOS: uma análise discursiva da série 8 em Istambul - Histher, Fernanda Cristina (2023)
This research is focused the forms and meanings of silence and to the ways in which silencing is manifested in female discourses present in the Muslim series 8 in Istanbul. The corpus comprises dialogue clippings from the referred series, shown on the Netflix platform in the year 2020. The goal is to identify and point the patriarchal visibility in family, religious, and cultural institutions predominant throughout the narrative, as well as to describe the way that silencing constructs meanings and veiled effects of subjection to the discourse materialized in culture. The theoretical assumptions of Discourse Analysis (DA) underlie the concepts addressed in this research, under studies based on Orlandi (2007, 2012) and Pêcheux (1997). The contributions of Althusser (1980) also supported our research, as well as Freud (1905) and Lacan (1953), bringing the unconscious silenced to integrate the singularity of the subjects as a otherness symbolic. In the course of our analyzes we observed that the female voice is silenced and sedimented by discourses already said and socially instituted to a greater or lesser extent, regardless of culture, in this study specifically, we dedicated ourselves to listening to the voice of the protagonist of the series, Meryem, inserted in the Muslim culture.